CONCEPTUAL FRAMEWORK FOR DEVELOPING AN ADAPTATION STRATEGY FOR BUSINESSES TO THE DIGITAL TRANSFORMATION OF THE ECONOMY (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The digital transformation of the economy is an inevitable process that causes significant changes in all spheres of activity of business entities. Adaptation to the new conditions of the digital economy becomes vital to ensure competitiveness and sustainable business development. However, the problems of forming an adaptation strategy for businesses to the digital transformation of the economy are relatively new in domestic practice and require scientific and methodological substantiation.The purpose of the article is to scientifically substantiate the concept of forming an adaptation strategy for businesses to the conditions of the digital transformation of the economy. The study is based on the development of existing theories of adaptation, strategic management, and the digital economy.The conceptual framework for adapting the core of business development to the conditions of the digital transformation of the economy is substantiated. The proposed concept is based on a process approach and envisages making appropriate changes in three key components: resource, business model, and strategic. This allows comprehensively covering the most important aspects of the entity's activity and ensuring systematic adaptation to the challenges of digital transformation.The concept of forming an adaptation strategy for businesses in the conditions of the digital transformation of the economy is developed. Its goal, objectives, principles, and objects of changes are determined. The methodological basis of the concept includes a set of methods that support the necessary changes in the components of the core of development under the influence of the digital transformation of the economy.The implementation of the proposed concept through a set of defined tasks (assessment of readiness, digital maturity, feasibility of adaptation, digital strategizing, business model transformation, and development of a digital adaptation strategy) will allow businesses to effectively adapt to the new conditions of the digital economy, ensuring the necessary quantitative and qualitative changes in the internal environment.Further research should be aimed at improving the methodological tools for assessing the readiness and digital maturity of businesses, developing practical recommendations for transforming business models in line with the requirements of the digital economy, and forming effective digital adaptation strategies, taking into account the specifics of activities and industry characteristics.
Keywords: adaptation; businesses; digital transformation of the economy; adaptation strategy; concept; core of development